Compost Fertilizer Machine - Easy Green Compost Sdn Bhd / Nurul Syafiqah Othman - Othman, Nurul Syafiqah (2020)
According to the waste management and public cleansing corporation, Malaysia generated 38142 tonnes of food waste per day in 2018 increase from 19000 tonnes in 2005. It is almost half which is 44.5% is food waste that is includes organic materials that can be composted. In Malaysia, industry of composting has been growing in popularity. Easy Green Compost Sdn Bhd is the names of our company. The names is given based on the description of our product which is compost fertilizer machine that convenience for the customer to used. Besides, “Green Compost” means our produce the end product that save our environments from green house emission by producing compost fertilizer from food waste. The concept of our product focusing in the improvement of technology from existing product compost machine in the market. Easy Green Compost Sdn Bhd is a company that produce a products in the composting industry. We are producing a product based on the improvement of technology which is aligned with the customer’s need. The concept of our product to accelerate the composting process and at the same time produce a quality compost fertilizer by using technology organic catalyst “Sustained Release” that is implemented in our compost fertilizer machine. We are believed that our company’s product are being marketed to attract potential customers and provides a benefits for both company and fulfil their needs to overcome customer’s problem.